Analysis of Compound Content of Ethanol Extract of Butterfly Pea Flower (Clitoria ternatea L.) Using Thin Layer Chromatography Method: A Systematic Literature Review - Rahma, Aliffia Dwi; Dinda Revalina Putri; Khesya Shafira Maurizkya; Novi Lavly Fairish; Wianda Azzahra Audia; Widya Fatmala; Lia Fikayuniar (Eureka Herba Indonesia, 2024)
The butterfly flower (Clitoria ternatea L.) is an herbal plant that is widely used in traditional medicine in Indonesia. The chemical compounds in butterfly pea flowers are thought to have various biological activities, such as antioxidant, anti-inflammatory, antibacterial and antidiabetic. Analysis of the compound content in butterfly pea flower extract can be done using various methods, one of which is thin layer chromatography (TLC). The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) analysis of the compound content of ethanol extract of butterfly pea flowers using the thin layer chromatography method. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. The ethanol extract of butterfly pea flowers contains various groups of secondary metabolite compounds, such as flavonoids, saponins, terpenoids and tannins. These compounds are thought to have various biological activities, such as antioxidant, anti-inflammatory, antibacterial and antidiabetic.